Peran Value Co Creation dalam Consumer Engagement Pada Pengguna Shopee di Kota Medan - Joyce Alicia; Maharani Aruan; Ririn Pradilla Surbakti; Yosefira Aurel Putri; Muhammad Aulia Rifki Nst; Onan Marakali Siregar; Afrila Mulyati Siregar (CV. ITTC INDONESIA, 2024)
Value co-creation is a concept where customers play an active role in creating value with the company. The role of Value Co-Creation in Consumer Engagement in companies like Shopee is very important. This research uses qualitative methods to explore how Shopee applies value co- creation in increasing consumer engagement. Through in-depth interviews and content analysis, it was found that active customer engagement in various company activities, such as gamification and product reviews, contributed significantly to increased customer satisfaction and loyalty. The research results show that customer participation in value creation not only increases satisfaction but also strengthens emotional attachment and trust in the brand. These findings emphasize the importance of value co-creation strategies in efforts to increase consumer engagement in the digital era.